Appealing. The Biden Doctrine in the "Cold Democracy" Age - Amedeo Gasparini (Universidade Estadual de Alagoas, 2022)
Western democracies have lost their compass. They are cold and with no appeal; not looked upon as an efficient and effective model of governance. The Biden Doctrine might be defined as Joe Biden's worldview divided between democracy and authoritarianism, as well as his attempt to make democracy attractive by having it deliver effectively on people's concerns and needs. The Doctrine is also characterized by a commitment to the respect of human rights: its concern is not spreading democracy, but to show that liberal democracy can effectively deliver at home and abroad more efficiently than authoritarian systems. The Biden Doctrine must not only focus on the revival of democracy but also face the challenge posed by authoritarianism's appeal. The Doctrine must stand up against the authoritarian rule, to promote liberal democratic government and respect for human rights as a solution to the distrust of democracy, in the era of cold democracies.